Manual of environmental microbiology - Hurst, Christon J. 1954-; Crawford, Ronald L., 1947-2018 (ASM Press, 2007)
Thoroughly updated and revised, this third edition assembles the most definitive information on microbes in air, water, and soil and their impact on human health and welfare.